PLURALISME HUKUM INDONESIA BAGI HAKIM TATA USAHA NEGARA: ANTARA TANTANGAN DAN PELUANG - Endri Endri (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2020)
This research is explaining the challenges and opportunities for the resolution of administrative disputes by administration judges as executors of the judicial authority to examine, decide and resolve disputes in the reality of legal pluralism in Indonesia. To analyze the legal issues, this research presents the concepts of legal pluralism and then sees how the implications for the implementation of the authority of administration judges in the process of dispute resolution. This study is important because law enforcement and justice by the judiciary in the midst of legal pluralism have provided challenges and opportunities for judges in order to ensure court decisions are able to answer legal needs and provide substantive justice for justice seekers.